2012
DOI: 10.3989/scimar.03522.05a
|View full text |Cite
|
Sign up to set email alerts
|

Particular features of gonadal maturation and size at first maturity in <i>Atrina maura</i> (Bivalvia: Pinnidae)

Abstract: SUMMARY: The gonadal maturation of Atrina maura was examined by means of histological analysis and quantitative criteria. Particular features not previously described for this species are reported in this study: in both males and females the undifferentiated stage is absent and there is massive gamete resorption when the seawater temperature reaches 25°C; in males, there is continuous spawning concurrent with other gonadal development stages and the adipogranular cells surrounding the acini walls decrease with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Although these stages were excluded from the present study, white clams living in SR showed atretic oocytes at intensities more than 300% higher relative to those of SL and EB clams, which may significantly affect the ovarian cycle and impair spawning. According to Motavkine and Varaksine (1983), this high prevalence of prespawning atresia may result from unfavorable environmental conditions, such as a nutritional deficit (e.g., Fearman et al 2009), abnormal temperatures (e.g., Camacho‐Mondragón et al 2012), or exposure to pollutants (e.g., Vaschenko et al 1997; Ortiz‐Zarragoitia and Cajaraville 2010; Yee‐Duarte et al 2018). According to Beninger (2017), there are few studies correlating metal exposure with an increase of atretic oocytes in bivalves, especially those in the natural environment—an aspect addressed in this paper.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these stages were excluded from the present study, white clams living in SR showed atretic oocytes at intensities more than 300% higher relative to those of SL and EB clams, which may significantly affect the ovarian cycle and impair spawning. According to Motavkine and Varaksine (1983), this high prevalence of prespawning atresia may result from unfavorable environmental conditions, such as a nutritional deficit (e.g., Fearman et al 2009), abnormal temperatures (e.g., Camacho‐Mondragón et al 2012), or exposure to pollutants (e.g., Vaschenko et al 1997; Ortiz‐Zarragoitia and Cajaraville 2010; Yee‐Duarte et al 2018). According to Beninger (2017), there are few studies correlating metal exposure with an increase of atretic oocytes in bivalves, especially those in the natural environment—an aspect addressed in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…Photomicrographs were analyzed using SigmaScan Pro version 5.0 (Systat Software, Inc.) and Image J version 1.53k (National Institutes of Health). The sex and gonadal development stage of each clam were determined according to Camacho‐Mondragón et al (2012) and Aguilar‐Cruz et al (2020).…”
Section: Methodsmentioning
confidence: 99%
“…A. ventricosus: Baqueiro et al, 1982bFélix-Pico, 1993Massó-Rojas, 1996;Ruiz-Verdugo et al, 2000. Atrina maura: Fajardo-León, 1998Camacho-Mondragón et al, 2012;Camacho-Mondragón, 2014;Gómez-Valdez, 2019. Pinna rugosa: Fajardo-León, 1998Gómez-Valdez, 2019.…”
Section: Biological Characteristics Of the Mollusks From Bahia Magdalenamentioning
confidence: 99%